2022
DOI: 10.21037/atm-22-909
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metformin on pregnancy outcome, metabolic profile, and sex hormone levels in women with polycystic ovary syndrome and their offspring: a systematic review and meta-analysis

Abstract: Background: Researches of the efficacy and safety of metformin on long-term pregnancy outcomes remains conflicted. We performed an updated systematic review and meta-analysis to systematically investigate the effect of metformin treatment on pregnancy outcome, metabolic profile, and sex hormone characteristics in women with polycystic ovary syndrome (PCOS) and their offspring. Methods:The PubMed, Embase, and Cochrane Library databases were searched from inception to July 10, 2021 with the keywords "metformin",… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…These findings are significant considering that women with PCOS are at an increased risk of developing complications such as gestational diabetes mellitus (GDM), PIH, and preterm delivery [ 26 , 17 ]. The findings of this study are consistent with a number of high-quality studies supporting the benefits of MTF in reducing the risk of pregnancy complications [ 19 ].…”
Section: Reviewsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are significant considering that women with PCOS are at an increased risk of developing complications such as gestational diabetes mellitus (GDM), PIH, and preterm delivery [ 26 , 17 ]. The findings of this study are consistent with a number of high-quality studies supporting the benefits of MTF in reducing the risk of pregnancy complications [ 19 ].…”
Section: Reviewsupporting
confidence: 91%
“…It was found that MTF treatment during pregnancy reduced the risk of PIH, preeclampsia, macrosomia (abnormally large birth weight), and preterm delivery compared to placebo [ 19 , 14 , 20 ]. These findings are significant considering that women with PCOS are at an increased risk of developing complications such as gestational diabetes mellitus (GDM), PIH, and preterm delivery [ 26 , 17 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Metformin, the most widely used insulin sensitizer for PCOS, reduces hepatic glucose production, inhibits gluconeogenesis and adipogenesis, improves peripheral tissue sensitivity to insulin, and prevents excessive insulin activity in the ovary [153]. Numerous studies have shown that metformin not only reduces weight and metabolic disorders but also corrects menstrual patterns, restores ovulation, and even improves chances of pregnancy [154]. Evidence-based guidelines recommend the use of metformin in obese, insulin-resistant women with PCOS to manage weight and endocrine and metabolic disorders, in conjunction with lifestyle adjustments [155,156].…”
Section: Insulin Sensitization Therapy Metforminmentioning
confidence: 99%
“…Most medications prescribed for pregnant and lactating women are “off-label” because most of the clinically approved medications do not have appropriate drug labeling information ( Ren et al, 2021 ). The limited evidence indicates the long-term safety of the fetus exposed to metformin excluding mild adverse anthropometric profiles (sex hormone binding globulin levels and long-term body mass index in offspring) ( Roy and Sahoo, 2021 ; Zhu et al, 2022 ). Although the FDA has not completely ruled out the risk of metformin in pregnancy, “these studies cannot establish the lacking metformin-associated risk because of methodological limitations, including the small sample size and inconsistent comparator groups” ( https://packageinserts.bms.com/pi/pi_glucophage.pdf ), many of the reviewed studies concluded that metformin is a safe choice at the beginning of pregnancy without persuasive evidence of increased risk for miscarriages or congenital malformations ( Quadir, 2021 ).…”
Section: Introductionmentioning
confidence: 99%